The Influence of Celebrity Endorsement, Brand Image and Brand Equity on Purchase Intention of Adidas Shoes - Javier Goldin; Rodhiah Rodhiah (International Journal of Management Science and Application, 2025)
This research examines the influence of celebrity endorsements, brand image, and brand equity on the purchase intention of Adidas shoes.  This research used a quantitative research method with a purposive sampling technique involving 92 respondents who had purchased Adidas shoes at least once.  Data was collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS.  The results indicate that celebrity endorsement does not have a significant effect on purchase intention (β = 0.149, p > 0.05).  Brand image has been proven to have a positive and significant impact on purchase intention (β = 0.093, p < 0.001), whereas brand equity does not show a significant effect (β = 0.337, p > 0.05).  The coefficient of determination shows that these three variables influence purchase intention by 22.1%, whereas 77.9% are influenced by other variables.  These findings indicate that, in the Indonesian market, brand image plays a more significant role in influencing purchase intention than celebrity endorsement and brand equity for Adidas shoe products.  The results of this research have important implications for Adidas’ marketing strategy in Indonesia, particularly in terms of resource allocation and brand image development.